ANALIZA ŚWIADOMOŚCI KONSUMENTÓW W ZAKRESIE ZRÓWNOWAŻONEJ DZIAŁALNOŚCI BIZNESOWEJ ORGANIZACJI - Anna KURZAK-MABROUK (Nowoczesne Systemy Zarządzania, 2017)
The idea of sustainable development is based on three principles: ecological, social and economic. The key task of all organizations is to skilfully carry out activities in these three areas, because only then it is possible to build a long-term strategy that will be possible to develop effectively. The article consists of a theoretical and practical part. The first explains what is sustainable development and sustainable business generating sustainable products. The practical part shows how consumers perceive the efficient implementation of activities in the field of sustainable development in organizations.